PENGARUH TRANSFER PRICING DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2020-2022 - Candra, Ni Komang; Indonesia, Indonesia; Tallane, Yoan Yohana (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Tax avoidance is an effort made by companies to reduce taxes but does not violate applicable laws or regulations. This study was conducted to determine the effect of transfer pricing and leverage carried out by companies on tax avoidance efforts in property and real estate companies on the Indonesia Stock Exchange using secondary data with the samples used being balance sheets and profit and loss reports. This study uses samples from property and real estate companies listed on the Indonesia Stock Exchange for the 2020-2021 period. The transfer pricing variable is known to have no significant influence on tax avoidance and the leverage variable is also concluded to have no significant influence on tax avoidance. This can be seen in the results of statistical tests, normality tests, autocorrelation tests, T and F significance tests, as well as coefficient of determination tests which explain the existing variables.